NPK fertilization, biomass distribution and number of potatoes minitubers in the greenhouse - Flores-López, Román; Casimiro-Marín, Maricela; Sotelo-Ruiz, Erasto; Rubio-Covarrubias, Oswaldo; López-Delgado, Humberto (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of this research was to evaluate the response of the potato (Solanum tuberosum) to the fertilization of nitrogen (N), phosphorus (P) and potassium (K), in the accumulation of biomass, harvest index and number of tubers under conditions of hydroponics under greenhouse. The experimental design used was the San Cristóbal, with 12 treatments. The variables that were evaluated were: leaf biomass, stem, root, stolon and tuber, harvest index and number of tubers. The biomass distribution in all the treatments, with respect to the total biomass, varied from 9.88 to 13.1% in leaf; 1.83 to 4% stem, 1.9 to 4.9% root, 0.8 to 1.31% stolon and 77.6 to 83.6% in tuber. The fertilization treatment with 250N-80P-300K mg L-1 obtained the highest accumulation of total biomass per plant, 63.54 g; for leaves, 6.78 g, stem 2.36 g, stolon 0.5, root 1.2 g and tubers 52.56 g. While the treatment that presented the highest harvest index was T2 (200N-30P-250K) with 0.83, only different from the treatments T7 (100N; 130P; 350K) and T11 (150N; 180P; 300K) with 0.77 and 0.78, respectively. The harvest index was not related to the number of tubers per plant, since the treatments with the highest number of these were T8 (200N-130P-250K) with 18.6 tubers and T12 (150N-80P-400K) 18.2, with an index harvest of 0.82, while the T3 with the highest index (0.83) only produced 13.7 tubers per plant.